Does Leadership Style Make a Difference? Linking HRM, Job Satisfaction, and Organizational Performance. (June 2014) - Vermeeren, Brenda; Kuipers, Ben; Steijn, Bram
With the rise of New Public Management, public organizations are confronted with a growing need to demonstrate efficiency and cost-effectiveness. In this study, we examine the relationship between public organizational performance and human resource management (HRM). Specifically, we focus on job satisfaction as a possible mediating variable between organizational performance and HRM, and on the influence of a supervisor's leadership style on the implementation of Human Resource (HR) practices. Drawing on a secondary analysis of data from a national survey incorporating the views of 6, 253 employees of Dutch municipalities, we tested our hypotheses using structural equation modeling. The findings indicate that (a) job satisfaction acts as a mediating variable in the relationship between HRM and organizational performance and (b) a stimulating leadership style has a positive effect on the amount of HR practices used, whereas (c) a correcting leadership style has no effect on the amount of HR practices used.